COMPOST FERTILIZER USE ON THE GROWTH AND YIELD purple eggplant (Solanum melongena L.) - Ouril, Delviana Nguda; ., Sutoyo; Hapsari, Ricky Indri (Universitas Tribhuwana Tunggadewi, 2014)
Eggplant is a vegetable plant that has a shape and color that diverse and widely cultivated in tropical and subtropical climates (mountain areas). The purpose of this study is to determine and study the effect of the optimal dose of fertilizer or compost to plant eggplant purple. The research was conducted in the village of Tlogowulan, Lowokwaru, Malang, East Java, which began in February to May 2014 in the study design environment using single factor RAK with 5 treatments and 4 replications, while the dose of the treatment applied is 4 levels of compost and 1 control. Parameters observed plant height, number of leaves, fruit weight and fruit weight per hectare plantation. If the results of analysis of variance was significantly different then followed by LSD test level of 5%. The results showed treatment of municipal solid waste compost significantly affect plant height (2, 4, 6, 8, 10 and 12 mst), number of leaves (4, 6, 8, 10 and 12 mst), planting fruit weight (10 and 12 mst) and fruit weight per hectare (12 mST). Municipal solid waste compost dose that gives the highest yield for each parameter eggplant purple plant is 1000 grams / plant.